Trend in resistance to beta-cypermethrin in Aedes albopictus and preliminary strategies of beta-cypermethrin use in Xuhui District， Shanghai - ZHU Wei; LIU Yao; LIU Xiangyu; LIU Hongxia (Shanghai yufang yixue, 2022)
ObjectiveTo investigate the resistance to beta-cypermethrin in Aedes albopictus in Xuhui District， Shanghai， China， and determine the effects of insecticide components， concentration and distance on eliminating resistant population of Aedes albopictus in ultra-low volume （ULV） spray， which would provide scientific evidence for effective mosquito control strategy and rational use of beta-cypermethrin.MethodsLarval impregnation method recommended by the World Health Organization was used to determine the drug resistance in Aedes albopictus larvae to calculate the median lethal concentration （LC50） of insecticides to Aedes albopictus larvae. The resistance to insecticides in female adults of Aedes albopictus was measured by the adult mosquito contact tube method recommended by the World Health Organization， and the 24-hour mortality （%） of female mosquitoes caused by insecticides was measured. Then the 24-hour mortality （%） of resistant female adults of Aedes albopictus due to beta cypermethrin monotherapy and compound agents was calculated by ULV spray.ResultIn 2016， 2017， 2019 and 2021， the resistance ratio in Aedes albopictus larvae to beta-cypermethrin was 9.22， 68.22， 37.33 and 59.22， respectively. In 2021， the 24-hour mortality of Aedes albopictus female adults was 62.07%. ULV sprayer experiments were performed using 4.5% beta-cypermethrin （single dose） and 12.0% beta-cypermethrin-chlorpyrifos （compound dose）. The 24-hour mortality increased with the concentration of the insecticides. The overall mortality caused by compound was higher than that by single dose. The mortality were 24.24%， 31.60% and 97.83% at the concentrations of 0.045 0%， 0.067 5% and 0.090 0% for single dose， respectively， and 58.87%， 61.62% and 90.00% at the concentrations of 0.12%， 0.18% and 0.24% for compound dose， respectively. There was no significant difference in mortality when spraying distance was 10 m， 30 m and 50 m.ConclusionAedes albopictus in Xuhui District is developed varying resistance to beta-cypermethrin. It warrants to strengthen the monitoring on insecticide resistance to formulate scientific and reasonable strategy for insecticide use. and reduce the resistance level of the Aedes albopictus to beta-cypermethrin. Compound dose is recommended to improve the effect. In addition， comprehensive treatment may be adopted to reduce the resistance.